Penelitian pengaruh cuaca terhadap sifat tegangan putus, perpanjangan putus dan kekerasan sol karet cetak dengan alat weather o-meter - Musthofa, Hadi (Majalah Kulit, Karet, dan Plastik, 1994)
The aim of this research is to find out the effect of weathering exposure on the quality of moulding rubber sole by weather - ometer apparatus (in door weathering test). During indoor test by Weather - Ometer, the condition of research is kept constanly i,e. black panel at 50oC, dry bulb at 36oC, wet bulb at 26oC and humidity at 45 %. Specimen exposed taking over from the chamber for testing purpose were caried out every 25 hours and performed up to the limiting time at which specific physical properties change of the sample come out. The highest change of the speciments physical properties happened at the treatment of 100 hours, 125 hours Â and 150 hours.